2011
DOI: 10.1177/1420326x11419872
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Formaldehyde in new Danish Residential Buildings in Relation to WHO Recommendations and CEN Requirements

Abstract: It is uncertain if current Danish legislation regarding emission of formaldehyde from wood-based panels could assure that concentrations of formaldehyde in the indoor air of buildings containing the material would meet the World Health Organization (WHO) guideline. This is of particular concern since the recent recognition by International Agency for Research on Cancer that formaldehyde is carcinogenic to humans. Therefore, the purpose of this study was to determine whether residents of newly built Danish resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Most of the studies required passive sampling on the DNPH tubes [3,4,[40][41][42] over a period of several days to a week, except Jarnstrom et al (2006) [43], who used active sampling using a 0.005 M sulfuric solution at 2-4 L/min, followed by a derivatization with acetyl-acetone and quantification by a spectrometric method. Our study appears to be the first one to report continuous formaldehyde monitoring in a low-energy building.…”
Section: Comparison With Previous Aldehydes Measurements Performed Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies required passive sampling on the DNPH tubes [3,4,[40][41][42] over a period of several days to a week, except Jarnstrom et al (2006) [43], who used active sampling using a 0.005 M sulfuric solution at 2-4 L/min, followed by a derivatization with acetyl-acetone and quantification by a spectrometric method. Our study appears to be the first one to report continuous formaldehyde monitoring in a low-energy building.…”
Section: Comparison With Previous Aldehydes Measurements Performed Inmentioning
confidence: 99%
“…The airborne formaldehyde mean concentrations were determined in the newly finished buildings (19 µg m −3 ) after 6 months (21 µg m −3 ) and 12 months (26 µg m −3 ), highlighting an increasing trend once the building was occupied. In Denmark, Kolarik et al (2012) [41] measured the formaldehyde concentrations in 20 new Danish residential buildings with a geometric mean value of 40 µg m −3 . They reported that formaldehyde levels exceeded the WHO guideline value of 100 µg m −3 in two buildings.…”
Section: Comparison With Previous Aldehydes Measurements Performed Inmentioning
confidence: 99%
“…Several countries have adopted legislation regarding various aspects of building construction and IAQ issues. France [ 10 ], China [ 11 ], Denmark [ 12 ], South Korea [ 13 , 14 ], Japan [ 15 ], and Canada [ 16 , 17 ] have adopted regulations affecting IAQ directly or indirectly. For instance, since 2013, France requires all of the construction materials and interior decoration products sold in France to be labelled with a standardized label presenting information on the emission of volatile organic compounds (VOC) (e.g., formaldehyde) in order to provide clear and complete information about the products that consumers buy and install in their buildings [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale studies (>100 homes) have measured ranges of indoor and outdoor pollutants across representative samples of national housing stocks. [1][2][3] Typically these studies have used sampling methods that report a single, mean value across the measurement period (typically a single measurement or an aggregated value taken over a few days to weeks) and may involve either single pollutants 4,5 or a wide range of targeted pollutants. 1,3,6,7 Statistical analysis of such large-scale measurements can then help to determine the influence of building and occupant characteristics.…”
Section: Introductionmentioning
confidence: 99%